Anionically-Reinforced Nanocellulose Separator Enables Dual Suppression of Zinc Dendrites and Polyiodide Shuttle for Long-Cycle Zn-I2 Batteries - Liu, Wenhui; Ma, Hong; Zhao, Lingli; Qian, Weiwei; Liu, Bo; Chen, Jizhang; Yao, Yagang (Nano-Micro Letters, 2025)
Zn-I2 batteries have emerged as promising next-generation energy storage systems owing to their inherent safety, environmental compatibility, rapid reaction kinetics, and small voltage hysteresis. Nevertheless, two critical challenges, i.e., zinc dendrite growth and polyiodide shuttle effect, severely impede their commercial viability. To conquer these limitations, this study develops a multifunctional separator fabricated from straw-derived carboxylated nanocellulose, with its negative charge density further reinforced by anionic polyacrylamide incorporation. This modification simultaneously improves the separator’s mechanical properties, ionic conductivity, and Zn2+ ion transfer number. Remarkably, despite its ultrathin 20 μm profile, the engineered separator demonstrates exceptional dendrite suppression and parasitic reaction inhibition, enabling Zn//Zn symmetric cells to achieve impressive cycle life (> 1800 h at 2 mA cm−2/2 mAh cm−2) while maintaining robust performance even at ultrahigh areal capacities (25 mAh cm−2). Additionally, the separator’s anionic characteristic effectively blocks polyiodide migration through electrostatic repulsion, yielding Zn-I2 batteries with outstanding rate capability (120.7 mAh g−1 at 5 A g−1) and excellent cyclability (94.2% capacity retention after 10,000 cycles). And superior cycling stability can still be achieved under zinc-deficient condition and pouch cell configuration. This work establishes a new paradigm for designing high-performance zinc-based energy storage systems through rational separator engineering. Highlights: 1 Straw-derived carboxylated nanocellulose separator is modified by anionic polyacrylamide to further enhance the negative charge density. 2 The separator exhibits ultrathin profile and exceptional mechanical strength, as well as enabling rapid zinc ion transport. 3 The separator can not only effectively inhibit zinc dendrites and parasitic reactions but also significantly suppress polyiodide shuttle via electrostatic repulsion, contributing to remarkable performance of Zn-I2 batteries even under high mass loadings.